2009
DOI: 10.1002/cne.22196
|View full text |Cite
|
Sign up to set email alerts
|

Inward rectifier channel, ROMK, is localized to the apical tips of glial‐like cells in mouse taste buds

Abstract: Cells in taste buds are closely packed, with little extracellular space. Tight junctions and other barriers further limit permeability and may result in buildup of extracellular K+ following action potentials. In many tissues, inwardly rectifying K channels such as the renal outer medullary K (ROMK) channel (also called Kir1.1 and derived from the Kcnj1 gene) help to redistribute K+. Using reverse‐transcription polymerase chain reaction (RT‐PCR), we defined ROMK splice variants in mouse kidney and report here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our results are consistent with previous reports from in vitro studies, and we are the first to demonstrate the functional difference between ROMK1 and ROMK2 in regulation of Na and K homeostasis in vivo. No specific role for the extended N terminus of ROMK3 has yet been identified, and we were not able to detect any ROMK3 expression in the kidneys of either WT, as reported previously (35), or Romk1 KO mice by Q-PCR.…”
Section: Discussionsupporting
confidence: 46%
“…Our results are consistent with previous reports from in vitro studies, and we are the first to demonstrate the functional difference between ROMK1 and ROMK2 in regulation of Na and K homeostasis in vivo. No specific role for the extended N terminus of ROMK3 has yet been identified, and we were not able to detect any ROMK3 expression in the kidneys of either WT, as reported previously (35), or Romk1 KO mice by Q-PCR.…”
Section: Discussionsupporting
confidence: 46%
“…20,21 Regulation of the extracellular ionic environment within the taste bud seems to be a key function. 22 Because of their role in terminating synaptic transmission, these cells are considered to play a supporting, glial-like function within the taste bud. 14 Recently, it has been suggested that type I cells may be responsible for the mediation of sodium transduction.…”
Section: Taste Bud Anatomy and Physiologymentioning
confidence: 99%
“…Type I cells, originally defined ultrastructurally as having electron-dense cytoplasm and elongate, pleomorphic nuclei, are believed to have glial-like functions [6]. These cells synthesize and deposit a powerful ecto-ATPase on their surfaces that degrades the transmitter released by other taste cells [7].…”
Section: Anatomy Of Taste Budsmentioning
confidence: 99%